Managing process chemicals, technology and equipment information for pilot plant based on Process Safety Management standard - Aziz, H.A. (Institution of Chemical Engineers, 2014)
Injuries, accidents or even fatalities while working in pilot plant are reported worldwide. The OSHA Laboratory Standard and Hazard Communication Standard have been used as a guideline to manage safety of laboratories and pilot plant. In spite of the implementation of these standards, incidents which result in injuries and property loss are continuously occurring. The implementation of OSHA Process Safety Management (PSM) Standard in pilot plant is expected to further reduce the risks of accidents. This paper presents a new system for managing process chemicals, technology and equipment information in pilot plant and the concept is developed based on Process Safety Information (PSI) element of PSM 29 CFR 1910.119(d). It provides organized strategies to manage documentations, communicate information, and written program for maintaining, revising and updating related information. Process and Instrumentation Diagram (P&ID) is used as a foundation for data management. Implementation of this system at the CO2 Hydrocarbon Absorption System pilot plant as a case study is examined and discussed. Â© 2013 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.